2018
DOI: 10.1055/s-0038-1627097
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cord Blood Magnesium Level at Birth on Non-neurologic Neonatal Outcomes

Abstract: Higher cord blood magnesium levels do not appear to have adverse non-neurologic effects on the neonate and may demonstrate improvement in neurologic outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 16 publications
0
5
0
1
Order By: Relevance
“…However, two larger reports by the Pediatrix Medical Group and the Canadian Neonatal Network showed no increase in NEC or SIP in relationship to any antenatal MgSO 4 exposure 13,14 . Recent meta-analysis and publications also supported these results 9,15,16 . As most evidences regarding association of antenatal MgSO 4 with gastrointestinal complications have been controversial, the role of antenatal MgSO 4 in association with gastrointestinal complications is not well established yet 8 .…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…However, two larger reports by the Pediatrix Medical Group and the Canadian Neonatal Network showed no increase in NEC or SIP in relationship to any antenatal MgSO 4 exposure 13,14 . Recent meta-analysis and publications also supported these results 9,15,16 . As most evidences regarding association of antenatal MgSO 4 with gastrointestinal complications have been controversial, the role of antenatal MgSO 4 in association with gastrointestinal complications is not well established yet 8 .…”
mentioning
confidence: 64%
“…Previous studies reporting the association of antenatal MgSO 4 with NEC and/or SIP have included extremely preterm babies born at less than 25-26 weeks of gestation 11,12 . Other studies reporting a lack of association between antenatal MgSO 4 treatment and NEC or SIP have included preterm infants born at ≤ 28-34 weeks of gestation [13][14][15][16] . We included infants born at 24-31 weeks of gestation, because the indication of antenatal MgSO 4 treatment protocol for fetal neuroprotection in our institute was those who were at risk of preterm birth at 24-31 weeks of gestation, and the objective of this study was to investigate whether these protocol changes might have any effect on the risk of NEC in this population.…”
Section: Discussionmentioning
confidence: 99%
“…[12] However, another secondary analysis of a prospective trial reported that newborns with higher magnesium levels did not show any adverse non-neurological effects. [19] Moreover, a meta-analysis of 5 randomized controlled studies concluded that there were no statistically signi cant differences in neonatal secondary outcomes, such as IVH, periventricular leukomalacia, NEC, RDS, ROP or chronic lung disease. [20] In the aforementioned secondary analysis study, although the combined outcome of death and severe NEC was associated with maternal antenatal MgSO 4 administration in infants who were GA less than 26 weeks, NEC alone was not associated with antenatal MgSO 4 .…”
Section: Discussionmentioning
confidence: 99%
“…12 However, another secondary analysis of a prospective trial reported that newborns with higher Mg levels did not show any adverse non-neurological effects. 20 Moreover, a meta-analysis of 5 randomized controlled studies concluded that there were no statistically significant differences in neonatal secondary outcomes, such as IVH, periventricular leukomalacia, NEC, RDS, ROP or chronic lung disease. 21 In the aforementioned secondary analysis study, although the combined outcome of death and severe NEC was associated with maternal antenatal MgSO 4 administration in infants who were GA less than 26 weeks, NEC alone was not associated with antenatal MgSO 4 .…”
Section: + Modelmentioning
confidence: 99%